Effectiveness of a physiotherapy self-management programme for adult patients with chronic non-specific low back pain in low- and middle-income countries: protocol for a systematic review and meta-analysis - Niri Naidoo; Alfred Musekiwa; Kabelo Kgarosi; Sergant Given Motha; Maureen Moyo-Chilufya; Karien Mostert (BMJ Open, 2024)
Introduction Chronic non-specific low back pain (CNLBP) is among the most common musculoskeletal system conditions reported worldwide; however, few studies are available from low- and middle-income countries (LMICs). Self-management is a set of tasks performed by the patient aiming at managing their symptoms and interference in activities, mood and relationships due to pain. A physiotherapy-guided self-management programme (SMP) following a biopsychosocial approach has been reported as effective and affordable in the management of CNLBP in high-income countries. The objective of this systematic review is to determine the overall effectiveness of SMPs for adults with CNLBP in LMICs.Methods and analysis In this systematic review, the Preferred Reporting Items for Systematic Reviews and Meta-Analyses-Protocol (PRISMA-P) guidelines will be followed. A three-step search strategy will be used to search the electronic databases (PubMed, MEDLINE, SPORTDiscus, Scopus and CINAHL, Academic Search Complete and PEDro) for randomised controlled trials assessing the effectiveness of physiotherapy-guided self-management for CNLBP among adult participants in LMICs. The processes of screening search results for eligible studies, extracting data from included studies and appraising will be done independently by at least two review authors. Random effects meta-analysis will be used to synthesise results and heterogeneity will be assessed using the I2 test statistic and χ2 test.Ethics and dissemination Ethics clearance was obtained for the broader PhD study on the development of a physiotherapy-guided SMP for adult people with CNLBP in Limpopo Province, South Africa. The results of the manuscript for this protocol will be published in peer-reviewed journals and also presented at conferences, symposia, and congresses.PROSPERO registration number CRD42023399572.